Soil physical attributes in forms of sowing the annual winter pasture and intervals between grazing - da Veiga, Milton; Balbinot Junior, Alvadi; de Oliveira, Daniela (Revista Ciência Agronômica, 2014)
The sowing of winter pastures in areas used for summer grain production and their management under direct cattle grazing can cause changes in soil physical attributes, whose intensity depends on the degree of soil mobilization, grazing interval, stocking rate and weather. To study these aspects it was conducted over four years an experiment in a randomized block with split plots design and four replications. In the main plots were applied two forms of sowing the annual winter pasture (direct seeding and seeding + harrowing) and, in the subplots, four intervals between grazing (7, 14 and 28 days and ungrazed). Undisturbed soil cores were sampled at the end of each grazing cycle, in the 0-0.05 m layer to determine the saturated hydraulic conductivity and aggregate stability and in the layers of 0-0.05, 0.05-0.10, 0.10-0.15 and 0.15-0.20 m depth to determine bulk density and classes of soil pores. The direct seeding of annual winter pasture increases hydraulic conductivity and reduces soil bulk density in relation to seeding + harrowing while dairy cows trampling increases soil density and reduces macroporosity in the most superficial soil layer. The variation in climatic conditions among grazing cycles affects the soil physical attributes more markedly than forms of sowing and intervals between grazing of the annual winter pasture.